Postpartum Depression and Children’s Social-Emotional Development from Early Childhood Through Young Adulthood - Morris, Jada Lavon (East Carolina University)
This thesis examines the long-term associations between maternal postpartum depression (PPD) and children’s social-emotional development from early childhood through young adulthood. Drawing on longitudinal data, I trace behavioral and psychological outcomes for children at ages 3, 5, 9, 15, and 22, focusing specifically on social-emotional behaviors and internalizing symptoms during childhood, and depression and anxiety in young adulthood. Utilizing a life course framework, this study theorizes that early maternal mental health plays a critical role in shaping children’s developmental trajectories, with consequences that accumulate and interact with broader structural and family contexts over time. Multiple regression models test whether the early exposure to PPD predicts later emotional difficulties, adjusting for important demographic and socioeconomic covariates. Findings suggest significant associations between maternal PPD and elevated internalizing symptoms in children, at ages 3, 5, 9, and 15; but there were no significant differences found in depression or anxiety symptoms in early adulthood. This research contributes to a more nuanced understanding of intergenerational mental health risks and emphasizes the importance of early identification and intervention in maternal mental health to support optimal child development.
Keywords: Sociology, Social Structure and Development; Health Sciences, Mental Health; Sociology, Social Research